Responsiveness of Criminal Law to Skimming Crimes in The Era of Industrial Revolution 4.0 (Four Point Zero) - Ahmad Suryadi (Jurnal Hukum Volkgeist, 2021)
This study aims to: 1)Analyze and understand the responsiveness of criminal law in entering the era of industrial revolution 4.0 (four point zero), 2)Enforcement of criminal law in cyber crime, criminal acts in cyber crime, criminal responsibility of cyber crime perpetrators. This research is normative-empirical research which is basically a merger between normative legal approach with the addition of empirical elements as the implementation of normative law in its action on every legal event that occurs in society. The results of this study show that cyber crime is a special crime. Cyber Crime has the intent as a crime in the realm of computer technology and internet networks as targets. The basis of law enforcement considerations in cyber crime is based on Law No. 11 of 2008 concerning Information and Electronic Transactions in the Act as amended into Law No. 19 of 2016 on Information and Electronic Transactions (ITE) on Information and Electronic Transactions. Criminal liability for perpetrators of cyber crime crimes always pay attention to the enactment of Law No. 11 of 2008 on Information and Electronic Transactions in as amended into Law No. 19 of 2016 on Information and Electronic Transactions (ITE) on Information and Electronic Transactions and pay attention to the methods of criminal law. In the process of law enforcement on cyber crime must always prioritize legal certainty as a form to provide protection and security in the process of transactions through the internet for the public at large.